Relationship between lean body mass and isokinetic peak torque of knee extensors and flexors in severely burned children - Tapking, Christian (Burns, 2019)
Objective Severe burns cause hypermetabolic responses and prolonged hospitalization, resulting in loss of body mass and muscle strength. This study aimed to determine whether long-term gains in lean body mass (LBM) after structured exercise programs are functionally meaningful and related to greater muscle strength in severely burned children. Study design LBM and muscle strength were measured at discharge and at 6, 12, 24, and 36 months after burn in 349 children. Body composition, including LBM, was measured via dual-emission X-ray-absorptiometry. Peak torque was measured using Biodex dynamometer at varying angular velocities (90, 120, 150, 180°/s). Pearson correlation analysis evaluated the association between LBM and peak torque. Results LBM progressively increased from discharge (32.5±11.5kg) to 36 months following injury (40.2±12.3kg). Peak torque and peak torque/LBM increased from discharge (56.4±34.0Nm and 1.7±34.0Nmkg−1) to 36 months after burn (102.3±43.8Nm and 2.5±0.7Nmkg−1, p<0.01 for both). LBM and peak torque at all angular velocities showed moderate/strong correlations, with 120°/s being the strongest (all time-points: R2≥0.57). Conclusion In severely burned children participating in a rehabilitative exercise program, gains in LBM over time are related to increases in muscle strength, suggesting that gained muscle mass is functional. Measurement of muscle strength at an angular velocity of 120°/s best reflects gains in LBM and should be considered for reliable measure of strength in future studies.
Available online 29 September 2018
Gesehen am 19.02.2019